KEPENTINGAN INDONESIA MERATIFIKASI THE CONVENTION ON THE RIGHTS OF PERSONS WITH DISABILITIES - Purwanto "; Yuli Fachri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describes about Indonesia’s interest on The ratification of Convention On The Rights Of Persons With Disabilities.(CRPD). Even though the UN already has conveotion about human right, but it is not enough to cover all the problems about human rights especially persons with disabilities. As develop country, Indonesia still had problems with disabilites people such as; the accesbility for public facilities, education, and participation on politics. Before Indonesia ratificated the CRPD, Goverment of Indonesia had made several policies about disabilites person, but this policies not enough to fulfill all the disabilities person rights.The theory that applied on this research are theory of foreign policy and national interest. The theory of foreign policy is an intrument of state to reach national interest and the the ideals of state for short/ long term goals. National Interest is a concept that every state that should have where it can give big contribution for establishment point of views the state about the external environmentThe study found that the interest of Indonesia ratified the CRPD is because this convention is represent all of rights for person with disabilites in every aspects, the UN members have concern about this problem. And the capabilities of Indonesia’s policies is not enough to handle about disabilities. Also this convention will give big impact to the right of disabilities person in the world. Further more, because of this convention, Indonesia legitimately made the CRPD as domestic law about disabilities (UU no. 19 tahun 2011), this is will be the foundation of Indonesia’s law about right of disabilites person.Keywords : Indonesia, CRPD, disabilities, and UU no. 19 tahun 2011